(untitled) (Revista de Ciências Agroveterinárias, 2017)
Knowledge of aspects related to the ecophysiology of plant species present in Caatinga is scarce, needing studies that allow the understanding of the adaptations made by plants to be able to survive under conditions of low water availability. Accordingly, this study was developed with the purpose of analyzing the gas exchange of ipê-roxo seedlings subjected to progressive water stress, through the suspension of irrigation, and rehydration. 12 month old plants, growing up in black plastic bags containing 5 kg of substrate, were subjected to two treatments: irrigated and water stress imposed by withholding water. The relative water content, stomatal conductance, transpiration rate, intercellular CO2 concentration, and photosynthetic rates were evaluated daily. After ten days remaining under this stress condition, irrigation was restored, and recovery was evaluated. Drought stress decreased rapidly and also progressively the relative water content, stomatal conductance, transpiration, carboxylation efficiency and photosynthesis of plants. An increase in intercellular CO2 concentration with increase of water stress was observed. After the resumption of water supply, the plants showed recovery of these physiological processes. Water stress did not affect the water efficiency use of plants.